2010
DOI: 10.1038/hr.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein is associated with cigarette smoking-induced hyperfiltration and proteinuria in an apparently healthy population

Abstract: Although cigarette smoking is known to be an important risk factor for renal disease, the mechanism by which smoking induces progressive renal disease in a healthy population has not been established. We hypothesized that oxidative stress (measured as 8-iso-prostaglandin F 2a , 8-iso-PGF2a), inflammation (highly sensitive C-reactive protein (CRP), hs-CRP) and nitric oxide may be associated with an alteration in the estimated glomerular filtration rate (eGFR) and proteinuria in otherwise healthy smokers. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
3
23
3
Order By: Relevance
“…There was a tendency for smokers to have a higher GFR than non-smokers. Our findings of a higher GFR and a lower risk of low GFR in smokers are consistent with those reported previously for general populations, especially in studies on workplaces [8][9][10]12]. Our results confirm that the elevated GFR in smokers was caused by smoking since a large reduction in GFR was observed after individuals stopped smoking.…”
Section: The Risk Of Low Gfr In Smokerssupporting
confidence: 82%
See 1 more Smart Citation
“…There was a tendency for smokers to have a higher GFR than non-smokers. Our findings of a higher GFR and a lower risk of low GFR in smokers are consistent with those reported previously for general populations, especially in studies on workplaces [8][9][10]12]. Our results confirm that the elevated GFR in smokers was caused by smoking since a large reduction in GFR was observed after individuals stopped smoking.…”
Section: The Risk Of Low Gfr In Smokerssupporting
confidence: 82%
“…Furthermore, many of the previous studies carried out in workplaces were cross-sectional in design [8][9][10][11][12]. The few longitudinal studies conducted in workplaces that have been conducted to date are limited to a small number of subjects [13] or to a short observational period [14].…”
Section: Introductionmentioning
confidence: 99%
“…If unable to have an age-adjusted control group, authors should at the minimum select from the literature a control group with characteristics similar to those of their participants and with similar GFR evaluation methods. Among the four studies reporting a GH threshold ,2 SDs of the median (of this systematic review), three used their own control group, with age adjusted to their study population (26)(27)(28). These three studies were performed in Japan and Taiwan, and GFR was indexed for body surface area, which is lower in Asian population (29).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that long-term hypertension, diabetes, hyperuricemia, renal arteriosclerosis, ischemic heart disease, and smoking can cause CKD [18][19][20][21][22][23]. In the present patient, multiple chronic diseases and a long-term smoking habit led to the occurrence of CKD.…”
Section: Discussionmentioning
confidence: 68%